In search of smoking guns: What makes income inequality vary over time in different countries? - Gustafsson, Björn; Johansson, Mats (University of Gothenburg, 2004)
Information about GDP per capita; GDP growth; total public expenditure as percent of GDP; percent public consumption; gini coefficient for equivalent disposable income; percent imports from developing countries; inflation; percent social security transfers; percent unionized; percent unemployed; female labor force participation rate; percent employed in industry; percent employed in agriculture; percent employed in service sector; percent of population aged 0-14 years; percent of population aged 15-64 years; percent of population aged 65 years or more for 16 industrialized countries during the period 1966-1994.

Purpose:

Find the reason to why income distribution change in industrialized countries.

Information about GDP per capita; GDP growth; total public expenditure as percent of GDP; percent public consumption; gini coefficient for equivalent disposable income; percent imports from developing countries; inflation; percent social security transfers; percent unionized; percent unemployed; female labor force participation rate; percent employed in industry; percent employed in agriculture; percent employed in service sector; percent of population aged 0-14 years; percent of population aged 15-64 years; percent of population aged 65 years or more for 16 industrialized countries during the period 1966-1994.

Syfte:

Söka orsaken till att inkomstfördelningen förändras i industrialiserade länder.
Förändringar i inkomstfördelningen i 16 industrialiserade länder 1966-1994
Keywords: developing countries; utvecklingsland; public expenditure; offentlig utgift; unemployment; arbetslöshet; trade union membership; medlemskap i fackförening; economic conditions; ekonomiska villkor; gross domestic product; bruttonationalprodukt; social security; social trygghet; inflation; inflation; age distribution; åldersfördelning; exports and imports; export och import; working women; förvärvsarbetande kvinnor; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Social Sciences; Samhällsvetenskap; Economics; Nationalekonomi